Work Environment and Training Transfer Intentions: Does Organizational Justice Moderate Their Relationship? - Muhammad Sarfraz; Zahid Hussain; Nausheen Syed; Faiza Rehman; Shah Rollah Bin Abdul Wahab; Muhammad Salihuddin (SAGE Open, 2021)
The work environment plays a vital role in the transfer of the newly attained knowledge, skills, and abilities (KSAs) at the workplace. In the past decades, a series of studies have investigated the direct relationship between the work environment and training transfer. Surprisingly, empirical findings noted the inconsistent relationship between the work environment and training transfer. Whereas, the moderating effect between these relationships has been less examined in the training transfer literature. Therefore, addressing this gap, the prospective study was designed to investigate the moderating role of organizational justice as a potential moderator between the relationships of work environment and training transfer in Pakistani large-scale textile organizations (LSTO). Survey data were collected from 336 front-line managers by employing a multi-stage sampling technique. Structural equation modeling and hierarchical regression technique were used to test the hypotheses. The results showed that supervisor support, peer support, and opportunity to use learning (i.e., dimensions of work environment) correlate positively with training transfer. The findings also confirmed the moderating role of procedural justice and distributive justice (i.e., dimensions of organization justice) between the relationship of work environment and training transfer. These results underscore the critical role played by organizational justice to enhance the transfer of training at the workplace. This study shows, for the first time, that how organizational justice is an important mechanism to stimulate the work environment to training transfer.